Fatigue and Impact Behavior of Friction Stir Processed Dual-Phase (DP600) Steel Sheets - Yilmaz, Mumin; Ozturk Yilmaz, Imren; Saray, Onur (Mdpi, 2024)
This study investigates the impact of friction stir processing (FSP) on the deformation behavior of 1.1 mm-thick DP600 steel sheets under both static and dynamic loading scenarios, with a focus on the automotive applications of the material. During the process, the large plastic shear strains imposed by FSP resulted in a maximum temperature of 915 degrees C, leading to a morphological transformation of the martensite phase from well-dispersed fine particles into lath martensite and grain refinement of the ferrite phase. DP600 steel showed an almost two-fold increase in static strength parameters such as the hardness value, yield strength, and ultimate tensile strength. As-received and processed DP600 steel exhibited a plastic deformation behavior governed by strain hardening. However, uniform elongation and elongation to failure after FSP took lower values compared to those of the as-received counterpart. Following the improvement in the static strength of the steel, the fatigue strength of the steel increased from 360 MPa to 440 MPa after the FSP. The finite-life fatigue fracture surfaces of the as-received samples were characterized by the formation of fine bulges due to the variation in the crack propagation path in the vicinity of the martensite particles/clusters. After FSP, the transformation of the martensite particles into coarser lath martensite also transformed the fracture surface into a step-like morphology. The microstructural evolution after FSP caused a decrease in the absorbed impact energy and maximum striker reaction force from 239 J and 37.6 kN down to 183 J and 33.6 kN, respectively. However, the energy absorption capacity of the processed steel up to failure was higher than the absorbed energy value of the as-received steel at the same impact displacement. The simultaneous decrease in both impact energy and reaction force is attributed to the higher cracking tendency of the processed microstructure due to the lower volume fraction of the ferrite phase. The experimental results reported in this study mainly show that FSP is an easy-to-apply and functional solution to significantly improve the static and cyclic strength of DP600 steel. However, it is clear that the reduced total impact energy absorption capacity after FSP may be taken into account in design strategies.
Keywords: dual-phase steel; DP600; friction stir processing; FSP; fatigue behavior; impact behavior